Disconnect between signalling potency and in vivo efficacy of pharmacokinetically optimised biased glucagon-like peptide-1 receptor agonists - Maria Lucey; Philip Pickford; Stavroula Bitsi; James Minnion; Jan Ungewiss; Katja Schoeneberg; Guy A. Rutter; Stephen R. Bloom; Alejandra Tomas; Ben Jones (Elsevier, 2020)
Objective: The objective of this study was to determine how pharmacokinetically advantageous acylation impacts on glucagon-like peptide-1 receptor (GLP-1R) signal bias, trafficking, anti-hyperglycaemic efficacy, and appetite suppression. Methods: In vitro signalling responses were measured using biochemical and biosensor assays. GLP-1R trafficking was determined by confocal microscopy and diffusion-enhanced resonance energy transfer. Pharmacokinetics, glucoregulatory effects, and appetite suppression were measured in acute, sub-chronic, and chronic settings in mice. Results: A C-terminally acylated ligand, [F1,G40,K41.C16 diacid]exendin-4, was identified that showed undetectable β-arrestin recruitment and GLP-1R internalisation. Depending on the cellular system used, this molecule was up to 1000-fold less potent than the comparator [D3,G40,K41.C16 diacid]exendin-4 for cyclic AMP signalling, yet was considerably more effective in vivo, particularly for glucose regulation. Conclusions: C-terminal acylation of biased GLP-1R agonists increases their degree of signal bias in favour of cAMP production and improves their therapeutic potential.